Sleep and daytime sleepiness in elite athletes and sedentary individuals - Jemal, M.; Trabelsi, K.; Boukhris, O.; Ammar, A.; Clark, C. C. T.; Chtourou, H. (Science & Sports, 2022)
Objectives The objectives of this study were to evaluate the duration and the quality of sleep, as well as daytime sleepiness, among different levels of Arab athletes (i.e., amateur, elite) and to compare sleep quality and duration and daytime sleepiness in athletes and sedentary individuals.